Does technological innovation matter to smart classroom adoption? Implications of technology readiness and ease of use - Long Kim; Rungrawee Jitpakdee; Wasin Praditsilp; Gulmira Issayeva (Journal of Open Innovation: Technology, Market and Complexity)
Smart classrooms represent innovative learning facilities that seamlessly blend physical reality with digital learning environments, facilitated by advanced technologies. As smart classrooms have significant impacts on individual learning and development, it is essential to comprehend technological innovation, technology readiness, perceived usefulness, trust, and perceived value on students’ adoption intention. To address this gap, 600 Thai university students were invited to join this research via questionnaire surveys. The collected data were analyzed using a path analysis technique. Findings from the analysis revealed two factors, namely perceived usefulness and perceived value positively predicted the student trust. Moreover, it was observed that technology readiness positively predicted both ease of use and perceived usefulness while ease of use positively predicted perceived usefulness and perceived value. Additionally, perceived value, student trust, and perceived usefulness determined students’ intention to adopt smart classrooms. Finally, the involvement of technological innovation enhanced the associations: (1) between perceived usefulness and adoption intention and (2) between trust and adoption intention. These results offer supportive evidence for the newly proposed theoretical model that highlights the associations between perceived value, trust, perceived usefulness, and adoption intention. Overall, this research contributes to the understanding of the associations between technological and psychological factors, paving the way for students’ decision to adopt smart classrooms in higher education.